Application of the Nested Enzyme‐Within‐Enterocyte (NEWE) Turnover Model for Predicting the Time Course of Pharmacodynamic Effects - Hiroyuki Takita; Adam S. Darwich; Amais Ahmad; Amin Rostami‐Hodjegan (Wiley, 2020)
The gut wall consists of many biological elements, including enterocytes. Rapid turnover, a prominent feature of the enterocytes, has generally been ignored in the development of enterocyte‐targeting drugs, although it has a comparable rate to other kinetic rates. Here, we investigated the impact of enterocyte turnover on the pharmacodynamics of enterocyte‐targeting drugs by applying a model accounting for turnover of enterocytes and target proteins. Simulations showed that the pharmacodynamics depend on enterocyte lifespan when drug‐target affinity is strong and half‐life of target protein is long. Interindividual variability of enterocyte lifespan, which can be amplified by disease conditions, has a substantial impact on the variability of response. However, our comprehensive literature search showed that the enterocyte turnover causes a marginal impact on currently approved enterocyte‐targeting drugs due to their relatively weak target affinities. This study proposes a model‐informed drug development approach for selecting enterocyte‐targeting drugs and their optimal dosage regimens.